Peran Kebijakan Dividen Dalam Memediasi Pengaruh ProfitabilitasTerhadap Nilai Perusahaan Studi pada Perusahaan yang Terdaftar dalam Jakarta Islamic Index (JII) Tahun 2020-2023: Studi pada Perusahaan yang Terdaftar dalam Jakarta Islamic Index (JII) Tahun 2020-2023 - Arina Innaka Rahmawati; Novi Mubyarto; Khairiyani Khairiyani (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The purpose of this study is to determine the Role of Dividend Policy in mediating the effect of Profitability on Company Value in the study of companies listed in the Jakarta Islamic Index (JII) in 2020-2023. The method used in this study is a quantitative method. This study uses secondary data in the form of annual reports of companies that are samples in the study and can be obtained from the Indonesia Stock Exchange website. The sample was taken using a purposive sampling technique totaling 13 companies. The data obtained and collected were then processed using SmartPLS Version 4 software. The data analysis techniques used are outer models and inner models. Based on the results of the Dividend Policy test, it has no effect on Company Value as reflected by PBV. And based on the results of the study, it shows that Profitability on Company Value through Dividend Policy indicates that Profitability in JII Companies in 2020-2023 can still show the internal Corporate Governance mechanism used to monitor Dividend Policy in order to achieve the company's goals, namely increasing Company Value.